Inequality in Total Returns to Work in Ukraine: Taking a Closer Look at Workplace (Dis)amenities - Olena Y. Nizalova (Institute for the Study of Labor (IZA), 2014)
This paper examines the importance of non-monetary dimensions of work in studies of inequality in total returns to work. Relying on the methodological advances in the field of multidimensional inequality and using the representative sample of Ukrainian industrial establishments over the period from 1994 to 2004, the paper shows that the focus on monetary compensation is too narrow. It ignores significant dynamics of inequality in workplaces. Analysis of such workplace conditions as risk of on the job injury, various benefits/amenities, and insecurities with wage payments, shows that the inequalities in these conditions do exacerbate inequalities in hourly wages. Workers in establishments paying highest hourly wages have enjoyed relatively greater reductions in the total workplace injury burden, greater retention of various benefits/ amenities, and relatively larger increases in wage payment security (decreased wage arrears), compared to the workers in the lowest paying establishments. These findings document the degree of an unequal shift away from work-centered provision of social services and highlight the importance of timely policy intervention.
Keywords: J81; D63; C14; 330; workplace injuries; disamenities; amenities; non-wage benefits; multidimensional inequality; non-parametric